2007
DOI: 10.1007/s10761-007-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Peopling the Recent Past in the Serra de L’Altmirant: Shepherds and Farmers at the Margins

Abstract: The region of the Serra de l'Altmirant in southeastern Spain, through its upland location and its rocky and scrub landscape, is strongly perceived as marginal-this mainly in contrast with the nearby fertile coastal plains between Valencia and Denia, busy with orange and vine production especially. A progressive colonization of the lower part of the Serra by weekend homes is starting to counter this image of marginality, but at the same time such constructions threaten the residual archaeology of a different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The levels of humidity are even higher in the valley where Moussai is located, and are affected by the rich aquifer, the dense vegetation and the steep slopes that block the sunlight for most of the day ( Figure 5). Contrary to what is known from ethnographic work in Spain (Creighton and Segui 1998;Christie et al 2007), where roof tiles were intentionally removed, in Moussai, although structures have suffered from extensive scavenging, it seems that it was not considered worthwhile to remove tiles. Although high humidity and lush vegetation make wildfires highly unlikely in this area, in contrast to other regions in the eastern Mediterranean, there are other factors that affect the condition of the settlement.…”
Section: The Sitementioning
confidence: 64%
See 1 more Smart Citation
“…The levels of humidity are even higher in the valley where Moussai is located, and are affected by the rich aquifer, the dense vegetation and the steep slopes that block the sunlight for most of the day ( Figure 5). Contrary to what is known from ethnographic work in Spain (Creighton and Segui 1998;Christie et al 2007), where roof tiles were intentionally removed, in Moussai, although structures have suffered from extensive scavenging, it seems that it was not considered worthwhile to remove tiles. Although high humidity and lush vegetation make wildfires highly unlikely in this area, in contrast to other regions in the eastern Mediterranean, there are other factors that affect the condition of the settlement.…”
Section: The Sitementioning
confidence: 64%
“…Ethnographie and historieal researeh in Spain (Creighton and Segui 1998;Christie et al 2007) and Sicily (Plueiennik et al 2004) has already demonstrated that the prineiple of uniformitarianism in faetors that influenee eultural behaviour cannot be applied satisfactorily. Although the settlement continued to be uninhabited for about two decades, people never stopped visiting the church, looking for valuables and usable items, destroying and dumping.…”
Section: Refuse Accelerating Ruination Destroying Remains and Estabmentioning
confidence: 99%
“…This is what happened in the last decades in the Spanish Mediterranean basin, especially in the lowlands: a dramatic change in land use, a likely important factor in its degradation (e.g., Hobbs et al 1995;Naveh 1998;Rundel 1998;Butzer 2005;González-Hidalgo et al 2007;García-Ruiz 2010). In the uplands, work has traditionally been less work intensive and therefore the risks produced by abandonment are also less pressing, but traditional ways of life fade away generation after generation (Creighton and Seguí 1998;Christie et al 2007). An ecologically fine-tuned Mediterranean environment (Butzer 1996) is increasingly under siege, and prospects for future management and preservation are doomed to fail as long as they are not accompanied by policies that keep people living and working the landscape.…”
Section: Introductionmentioning
confidence: 92%
“…Herding and cultivation in the lowlands are, thus, traditionally, complementary to each other (Butzer 2005), and a sustainable economic activity (Mangas 1992;Butzer 1996;Creighton and Seguí 1998;Sánchez Moreno 1998;Christie et al 2007), with different dimensions, ranging from mixed husbandry-farming activities to trasterminant short movements between close areas, the likely precedent of trashumance 20 (Pallaruelo 1993;López Sáez et al 2009). In all cases, regardless of the local specificities, the seasonal and varied character of these middle-altitude ranges made them very important in traditional rural economies, and especially important as summer pastures in traditional husbandry, well studied by Klein (1990), Bacaicoa et al (1993), Farnós et al (1993), Roigé Ventura et al (1993), Rubio et al (1993a, Pallaruelo (1993), or Fernández Temprado et al (1996.…”
Section: ) Cuevas Delmentioning
confidence: 99%
“…On the most basic level, household archaeology focuses on the individual domestic house, and although household archaeology is perhaps most easily identified with North America (King 2006, p. 295), archaeologists are working at this scale throughout the world, including in Latin America (e.g., Rocchietti 2008), England, Scotland, and Ireland (e.g., Giles and Giles 2007;Orser 2006b), Spain (e.g., Christie et al 2007), Australia (e.g., Allison 2003), and everywhere archaeologists excavate domestic structures.…”
Section: Scale In Historical Archaeologymentioning
confidence: 99%